Development of thermoplastic elastomer foams for footwear applications - Batrisyia Binte Mohamed Kamel (Nanyang Technological University, 2024)
Midsole foams play a crucial role in footwear, particularly in athletic shoes. Among the materials used for midsoles, Ethylene Vinyl Acetate (EVA) stands out as the most commonly utilized. The desired characteristics of EVA foams include a delicate balance of low density, adequate rebound, minimal wear loss, optimal hardness, and resilience. This project focuses on a specific aspect of EVA foam development through the incorporation of thermoplastic elastomer (TPE). Specifically, it explores the effects of blending Thermoplastic Vulcanizate (TPV) with EVA foam. The TPV content varied from 2.5 wt.% to 10 wt.%, while the amount of crosslinking agent (DCP) within the TPV blend ranged from 0% to 1.5%. This variation aims to investigate the impact of crosslinking content on the properties of both TPV and EVA/TPV foams. Characterization results revealed certain trends in physical properties such as hardness and density. Notably, there was an observable increase in percentage energy return with higher TPV content in EVA/TPV foams (~5%) as compared to conventional EVA foam, particularly with TPV containing 1.0 wt.% and 1.5 wt.% DCP. Morphological studies indicated that the TPV blend containing 1.0 wt.% DCP demonstrates optimal TPV morphology in terms of dispersion of POE (rubber) particles in the continuous thermoplastic region, aligning with findings from previous research. Furthermore, Differential Scanning Calorimetry (DSC) analysis indicated that with increased DCP content within the TPV blend, crosslinking within EVA and POE increased respectively, indicating successful dynamic vulcanisation.